Rationale for COVID-19 Treatment by Nebulized Interferon-β-1b–Literature Review and Personal Preliminary Experience - Mary, Aurélien; Hénaut, Lucie; Macq, Pierre Yves; Badoux, Louise; Cappe, Arnaud; Porée, Thierry; Eckes, Myriam; Dupont, Hervé; Brazier, Michel (Frontiers in Pharmacology, 2020)
The inflammatory response to COVID-19 is specifically associated with an impaired type I interferon (IFN) response and complete blockade of IFN-β secretion. Clinically, nebulization of IFN-α-2b has been historically used in China to treat viral pneumonia associated with SARS-CoV. Very recent data show that the use of inhaled type I IFN is associated with decreased mortality in Chinese COVID-19 patients. However, IFN nebulization is currently not standard in Europe and the United States. Therefore, our group has set up a project aimed to evaluate the possibility to nebulize IFN-β-1b (a drug currently used in Europe to treat multiple sclerosis via subcutaneous injections) and to assess the safety of this new mode of administration in SARS-CoV-2 infected patients. We present here literature data that allowed us to build our hypothesis and to develop collaboration between clinical pharmacists, intensivists and nebulization engineers in order to gain first pre-clinical and clinical experience of IFN-β-1b nebulization. After validation of the nebulization method and verification of droplet size compatible with nebulization, the method has been applied to 4 intensive care patients treated at our university hospital, for whom none of the COVID-19 therapies initially used in France led to significant clinical improvement. All patients exhibited negative viral carriage and experienced clinical improvement 7 to 16 days after having initiated nebulized IFN-β-1b inhalation therapy. No side effects were observed. All patients were alive within a 90-day follow-up. Although it is not possible to draw firm conclusions on treatment efficacy based on this case report, our study shows that pulmonary IFN-β-1b administration is feasible, with a good safety profile. This procedure, which presents the advantage of directly targeting the lungs and reducing the risks of systemic side effects, may represent a promising therapeutic strategy for the care of patients with severe COVID-19. However, our preliminary observation requires confirmation by randomized controlled trials.